Intercellular Interactions as Regulators of NETosis - Kazzaz, Nayef M.; Sule, Gautam; Knight, Jason S. (Frontiers in Immunology, 2016)
Neutrophil extracellular traps (NETs) are chromatin-derived webs extruded from neutrophils in response to either infection or sterile stimulation with chemicals, cytokines, or microbial products. The vast majority of studies have characterized NET release (also called NETosis) in pure neutrophil cultures in vitro. The situation is surely more complex in vivo as neutrophils constantly sample not only pathogens and soluble mediators, but also signals from cellular partners including platelets and endothelial cells. This complexity is beginning to be explored by studies utilizing in vitro co-culture, as well as animal models of sepsis, infective endocarditis, lung injury, and thrombosis. Indeed, various selectins, integrins, and surface glycoproteins have been implicated in platelet-neutrophil interactions that promote NETosis, albeit with disparate results across studies. NETosis can also clearly be regulated by soluble mediators derived from platelets such as eicosanoids, chemokines, and alarmins. Beyond platelets, the role of the endothelium in modulating NETosis is being increasingly revealed, with adhesive interactions likely priming neutrophils toward NETosis. The fact that the same selectins and surface glycoproteins may be expressed by both platelets and endothelial cells complicates the interpretation of in vivo data. In summary, we suggest in this review that the engagement of neutrophils with activated cellular partners provides an important in vivo signal or “hit” toward NETosis. Studies should therefore increasingly consider the triumvirate of neutrophils, platelets, and the endothelium when exploring NETosis, especially in disease states.